2016
DOI: 10.2147/ijn.s113589
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Bis(2-chloroethyl)-1-nitrosourea-loaded bovine serum albumin nanoparticles with dual magnetic resonance–fluorescence imaging for tracking of chemotherapeutic agents

Abstract: To date, knowing how to identify the location of chemotherapeutic agents in the human body after injection is still a challenge. Therefore, it is urgent to develop a drug delivery system with molecular imaging tracking ability to accurately understand the distribution, location, and concentration of a drug in living organisms. In this study, we developed bovine serum albumin (BSA)-based nanoparticles (NPs) with dual magnetic resonance (MR) and fluorescence imaging modalities (fluorescein isothiocyanate [FITC]-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Prakash et al demonstrated that 143 nm-sized HSA NPs showed 85.4% of cell viability in a MCF-7 cell line for 48 hrs 29. Wei et al tested 195 nm-sized BSA NPs to 300 μg/mL concentration in for 36 hrs in a MBR 262–1 cell line, and the BSA NP was more than 90% in cell viability 30. In line with other groups’ results, albumin NPs were strongly biocompatible materials, regardless of the origin of albumin, human, or bovine.…”
Section: Discussionmentioning
confidence: 99%
“…Prakash et al demonstrated that 143 nm-sized HSA NPs showed 85.4% of cell viability in a MCF-7 cell line for 48 hrs 29. Wei et al tested 195 nm-sized BSA NPs to 300 μg/mL concentration in for 36 hrs in a MBR 262–1 cell line, and the BSA NP was more than 90% in cell viability 30. In line with other groups’ results, albumin NPs were strongly biocompatible materials, regardless of the origin of albumin, human, or bovine.…”
Section: Discussionmentioning
confidence: 99%
“…Besides bound to NIR dyes, BSA can be further engineered with other functional agents via complexation, such as gadolinium (Wei et al, 2016 ; Yang et al, 2016 ; Chen et al, 2017a ; Zhou et al, 2017 ), manganese (Liu et al, 2017 ; Pan et al, 2017 ) and graphene's derivatives (Sheng et al, 2013 ). For example, hollow BSA was employed to fabricate a size-tunable Gd 2 O 3 @BSA conjugating Ce6 theranostics agent for MR imaging-guided PDT and PTT (Figure 3 ) (Zhou et al, 2017 ).…”
Section: Albumin-based Nanoformulationsmentioning
confidence: 99%
“…The MoS 2 -Gd-BSA theranostics agent exhibits a strong NIR absorbance and high r 1 relaxivity, which are helpful for PA and T 1 -weighted MR dual-modal imaging-guided PTT of cancer. Besides, a chemotherapeutic drug carmustine-encapsulated FITC-BSA NPs were prepared by desolvation/denaturation method and conjugated with a MR gadolinium(III) salt to form nanomedicine with dual imaging modalities (Wei et al, 2016 ).…”
Section: Albumin-based Nanoformulationsmentioning
confidence: 99%